Analisis Pengukuran Kinerja Keuangan dengan Metode Economic Value Added (EVA) pada Perusahaan Perbankan - Habib Sholeh; Merlyana Dwinda Yanthi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to find out about analyze and explain the financial performance of banking companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2021 using the Economic Value Added (EVA) method. This study is a quantitative descriptive research. The sample used in this research includes Bank Central Asia Tbk, Bank Negara Indonesia Tbk, Bank Rakyat Indonesia Tbk, Bank Mandiri Tbk, and Bank Tabungan Negara Tbk. The sampling technique employed in this research is purposive sampling with the following criteria: banking institutions that have gone public on the Indonesia Stock Exchange, banking institutions that have presented complete financial data and published it during the research period from 2017 to 2021, and banks included in the LQ45 index of the Indonesia Stock Exchange (BEI) for the period 2017-2021. The results of the research indicate that the five banking companies mentioned had positive EVA values during the period 2017-2021. This implies that these banking companies listed on the LQ45 Index of the Indonesia Stock Exchange for the period 2017-2021 demonstrated good performance and were able to create economic value added for investors. However, this research has several limitations, including the use of only one method to measure the financial performance of banking companies and a small sample size of 5 companies. Future research is recommended to employ multiple measurement methods to assess performance and increase the sample size to obtain better data.